THE PROFILE OF TWO SPECIMENS OF TROPICAL MARINE DIATOMS - Ham, Mwebaza
Kepulauan Seribu (Thousand Islands) has a very rich marine biodiversity of diatoms owing to its favorable temperatures and nutrients supplied from estuaries flowing into the ocean. So far, data on the identification and genetic profiling of the diatom in this area is not available yet they are facing a high risk of exploitation and extinction due to human activities. The present study aimed at profiling the existing specimens of diatoms based on their morphology, genetics, and biochemical compounds including lipids and carbohydrates. Two diatom specimens used were: NBO (isolated from Bokor island) and SUJ (isolated from Untung Jawa island). The methodology included; (i) culturing single cell cultures of the diatom specimens (ii) observing their morphology using a light microscope and SEM (iii) DNA profiling based on specific genes of LSU D2/D3, 18S rDNA-V4 and rbcL, and (iv) determining their lipids and carbohydrates content. The morphology of NBO cells was yellow-brown, oval, and bilaterally symmetric. The cells crept about on each other and on objective glass surface showing the characteristics of genus Navicula. Further genetic analysis of NBO, LSU D2/D3 sequence (554 bp) had 98% similarity to that of Navicula salinicola and 18S rDNA V4 sequence (430 bp) had 99 % similarity to Navicula salinicola and Bacillariophyta sp. Thus, NBO cells were identified as Navicula sp. The cells produced lipids containing 40.94% SFA, 40.05% MUFA, and 19.01% PUFA with the content of Omega-3 18.45%, Omega-6 0.59%, and Omega-9 2.82%. The yield of total carbohydrate produced by Navicula sp. NBO was 6.896%. The morphology of SUJ cells was yellow- brown, connected in long chains with a ring of spines and a convex valve like the cells of genus Skeletonema. Further analysis of SUJ, LSU D2/D3 sequence (597 bp) had 100% similarity to that of Skeletonema grethae, rbcL sequence (849 bp) had 98% similarity to that of Skeletonema grethae and 18S rDNA V4 sequence (433 bp) showed 99% similarity to that of both Skeletonema tropicum and Skeletonema cf. Pseudocostanum. Therefore, SUJ was classified to Skeletonema sp. Skeletonema sp. SUJ produced lipids containing 61.65% SFA, 24.44% MUFA, and 13.91% PUFA, with the content of Omega-3, 8.3%, Omega-6, 2.49% and Omega-9, 9.97%. The yield of total carbohydrate produced by Skeletonema sp. SUJ was 2.535%.